DETERMINAN TINGKAT PENGETAHUAN IBU TENTANG STATUS GIZI BALITA DI POSYANDU BOGENVIL KECAMATAN MERAL KABUPATEN KARIMUN TAHUN 2017 - Br Manurung, Tian Aprida; Ibrahim, Ibrahim (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
Toddler stage is the golden age of children due to their rapid growth of the body weight compared to the otherages. This period only happens once in child's life time, therefore it is called as window of opportunity. In this study, the researchers aim to determine the determination of the mothers' knowledge level on the nourishment status of their children specifically the ones under five years old. This research was designed to be an analytical research with cross sectional study approach. This study was conducted in Posyandu Bogenvil date on May 2017. The population was 98 toddlers and by using accidental sampling technique, 42 of them were taken as the sample. The research instrument used was questionnaire. After the data gathered from the questionnaires, further it was analyzed. The result reveals that the correlation between age and knowledge level is p-value=0,026<0,05, the education level and knowledge level is p-value=0,00<0,05 and information sources and knowledge level is p-value=0,346>0,05. From these findings, it can be inferred that age affects the knowledge level of mothers, in the same line, the education level and knowledge level do so. Meanwhile, there is no correlation between the sources of information and the knowledge level of the mothers. As the suggestion, the researchers encourage the mothers to accomplish their minimum 9 years of basic education hoping to develop their knowledge about nutrition status of children and to be able to implement their understanding in daily life.